Shareholder Activism by Government of Malaysia and Government-Linked Investment Companies: Some Case Studies - Ellias, Ahmad Fazil (2007)
This dissertation focuses on the relationship between shareholder activism and institutional investors in Malaysia since there is little literature on this topic with regard to Malaysian scenario. Therefore, the purpose of this dissertation is to explore how Malaysian institutional investors engage in shareholder activism by examining the roles assumed by the Malaysian Government-linked Investment Companies (GLICs). Specifically, the research seeks to explore four main areas of shareholder activism: To explore the forms of activism by the Government of Malaysia and Governmentlinked Investment companies (GLICs); To identify the factors that influences this form of shareholder activism; To identify the emerging Institutional investors in Malaysia; and To investigate the relationship between shareholders’ activism (by GLICs) and company’s performance. This dissertation tries to explore the new type of institutional investor as well as the new form of activism through case studies on the Malaysian Government-linked Investment Companies (GLICs). The findings show that the shareholder activism in Malaysia is a unique case because it has been led by the Malaysian Governmentlinked Investment Companies (GLICs). It also show that the GLICs’ shareholder activism have improved the financial performance of their investee companies. In addition, the study has managed to explore the new forms of activism among the GLICs namely Policy Guidelines and Macro-manage.